Biogas production under different inoculum to palm oil mill effluent ratio - Siti Noor Khaleeda Mhd Syahri,; Peer Mohamed Abdul,; Siti Rozaimah Sheikh Abdullah,; Raja Farzarul Hanim Raja Azmy, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Palm oil mill effluent (POME) is a wastewater generated from palm oil industries that rich with organic and nutrients which can becomes an excellent substrate for biogas production. A comprehensive study was carried out to study the effect of different ratio of inoculum to POME substrate for biogas production. In addition, the removal efficiencies of biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (AN), total nitrogen (TN) total suspended solid (TSS), volatile suspended solid (VSS) were also evaluated. Bio-methane potential (BMP) was used by manipulating temperature and HRT which were set to 28-32 °C and 30 days. The BMPs were operated under different ratio of inoculum to substrate at ratio of 20:80, 30:70 and 40:60. Highest cumulative biogas yield obtained was 1990 mL in the BMP containing 30:70 (inoculum:substrate) followed by the ratio of 40:60 with 1055 mL and 20:80 with 345 mL. Maximum TSS and VSS removal efficiency were 27% and 55%, recorded in 30:70 respectively, while in 40:60 and 20:80 were 23% and 12% and 8% and 51% respectively. The removal of TN was also high at 30:70 with 79% removal. Removal efficiency of COD was in BMP of 20:80 with 54% removal while BOD removal was seen the highest in 40:60 ratio BMP. Lastly, the AN were managed to be removed about 95% in 20:80 BMP. The results obtained in this study indicated that with different ratio od inoculum to POME substrate can enhance biogas production and quality of POME prior discharge to environment.